Evaluation of psychophysical condition of patients attending the “Caritas” Health Care Centre of the Roman Catholic Archdiocese - Pytka, Dorota; Doboszyńska, Anna; Syryło, Aneta (Polish Journal of Public Health, 2012)
Introduction. According to demographic analyses, people aged over 65, who will constitute 22.27% of the Polish society in 2030, are characterized by the most rapid growth of participation in the social structure. Given the shortage of geriatric care, ensuring proper care for the elderly person may increase the demand for health and nursing services at the place of residence as well as in the short- and long-term care facilities.Aim. The purpose of this research was to evaluate the psychophysical state among the patients of the Health Care Centre run by Caritas of the Warsaw Archdiocese in Warsaw.Material and methods. The survey was conducted in 2009 among 58 people who had given their consent for participation. The study group was limited to individuals whose mental and physical condition allowed them to participate in the research. The Activities of Daily Living (ADL) Scale and the Mini Mental State Examination (MMSE) were used as research tools. Descriptive statistics were applied to the data analysis.Results. Severely disabled people accounted for 56.90% of those who responded, 20.69% had a moderate disability, and only 22.41% were physically fit. The survey found 32.76% of the respondents with cognitive impairment suggesting the possibility of severe dementia, 29.31% of moderate dementia and 12.07% of mild dementia. Twelve and seven hundredths per cent of the patients were on the verge of dementia and 13.79% were diagnosed with cognitive impairment. There were no patients within this group who did not suffer from mental disorders.Discussion. Only a few studies carried out with the use of the same or functionally similar research tools related to the patients treated at a health care centre. Therefore, the discussion encompasses also the findings concerning health care forms similar to the discussed one, i.e. residential care homes, as well as the research tool that serves similar purposes, i.e. the Barthel scale.Conclusions. It was concluded that there was a link between the physical state and cognitive impairment suggesting the possibility of dementia occurring in patients living at a health care centre.